Scoping review of qualitative studies on family planning in Uganda. - Julie M Buser; Pebalo F Pebolo; Ella August; Gurpreet K Rana; Rachel Gray; Faelan E Jacobson-Davies; Edward Kumakech; Tamrat Endale; Anna Grace Auma; Yolanda R Smith (PLOS Global Public Health)
Family planning (FP) is an essential component of public health programs and significantly impacts maternal and child health outcomes. In Uganda, there is a need for a comprehensive review of the existing literature on FP to inform future research and programmatic efforts. This scoping review aims to identify factors shaping the use of FP in Uganda. We conducted a systematic search of eight scholarly databases, for qualitative studies on FP in Uganda. We screened the titles and abstracts of identified articles published between 2002-2023 and assessed their eligibility based on predefined criteria. We extracted data from the 71 eligible studies and synthesized the findings using thematic analysis and the Ecological Systems Theory (EST) individual, interpersonal, community, institutional, and policy-level determinants. Findings reveal the interplay of factors at different socio-ecological levels influencing family planning decisions. At the individual level, the most common determinants related to the EST were knowledge and attitudes of FP. Interpersonal dynamics, including partner communication and social support networks, played pivotal roles. Community-level factors, such as cultural norms and accessibility of services, significantly influenced family planning practices. Institutional and policy-level factors, particularly a healthcare system's quality and policies, also shaped use. Other themes included the intersection of HIV/AIDS on FP practice and Ugandan views of comprehensive abortion care. This scoping review underscores the intricate socio-ecological fabric shaping FP in Uganda. The findings highlight the need for targeted interventions to increase knowledge and awareness of FP, improve access to services, and address social and cultural norms that discourage contraceptive use. Policymakers and program implementers should also consider gender dynamics and power imbalances in FP programs to ensure they are equitable and effective.